Morphological and molecular characterization of Heterocapsa claromecoensis sp. nov. (Peridiniales, Dinophyceae) from Buenos Aires coastal waters (Argentina). Issue 4 (1st October 2020) - Sunesen, Inés; Rodríguez, Francisco; Tardivo Kubis, Jonás A.; Aguiar Juárez, Delfina; Risso, Antonella; Lavigne, Andrea S.; Wietkamp, Stephan; Tillmann, Urban; Sar, Eugenia A.
ABSTRACT: A new species of the marine dinophyte genus Heterocapsa Stein is described. Two clonal strains originating from Argentinean coastal waters were examined with light and electron microscopy and LSU and ITS rDNA sequence data were obtained. Heterocapsa claromecoensis sp. nov. is described as a distinctive species with a conical epitheca, a similar sized and rounded hypotheca, a single reticulate chloroplast situated in the periphery of the cell, and a large pyrenoid in the episome, above an ellipsoidal to rounded nucleus in the hyposome. The plate tabulation pattern of Po (pore plate), cp (cover plate), X (X-plate or canal plate), 5ꞌ, 3a, 7ꞌꞌ, 6c, 5s, 5ꞌꞌꞌ, 2ꞌꞌꞌꞌ was as for most other species of Heterocapsa. H. claromecoensis sp. nov. differs from all other species of Heterocapsa by the microarchitecture of two different types of organic body scales, which uniquely were different in height. Phylogenetic trees based on LSU and ITS rDNA sequences placed H. claromecoensis in a separate branch, with a sequence assigned to H. orientalis being the closest match based on LSU rDNA.